Neighborhood Search Considering Continuous Space Search - Gómez, A.T.; BODMANN, B.E.J. (Trends in Computational and Applied Mathematics, 2002)
The objective of this work is to present and discuss a dynamical optimization procedure based on the algorithm of self-consistent parametric inference, where the movement of one feasible solution to another is implemented in continuous mode. The approach is based on a generic parametrization of search space and uses the definition of a model independent metric, which guides progress of the procedure. One of the principal contributions of the proposed method is, if a solution is found it is optimal for the parametrization considered. This feature is guaranteed and proven by self consistency.